Case Report: Targeting of individual somatic tumor mutations by multipeptide vaccination tailored for HLA class I and II presentation induces strong CD4 and CD8 T-cell responses in a patient with metastatic castration sensitive prostate cancer - Zelba, Henning; Rabsteyn, Armin; Bartsch, Oliver; Kyzirakos, Christina; Kayser, Simone; Seibold, Marcel; Harter, Johannes; Latzer, Pauline; Hadaschik, Dirk; Battke, Florian; Golf, Alexander; Rettig, Matthew B.; et al. (Frontiers in Immunology, 2023)
While the first vaccine induced only one robust CD4+ T-cell response after 21 vaccinations, co-vaccination of HLA class I and II peptides induced multiple strong and durable CD4+ and CD8+ T-cell responses already after sixth vaccinations. The vaccine-induced immune responses were robust and polyfunctional. PSA remained undetectable for 51 months.The results presented here implicate that neoantigen-targeting vaccines might be considered for those cancer subtypes where therapeutic options are limited. Furthermore, our findings suggest that both HLA class I and II restricted peptides should be considered for future peptide vaccination trials.